Ekonomi Sirkular Islam: Integrasi Maqasid Syariah dalam Pengelolaan Sampah Berkelanjutan`` - Riza Anami; Khalilah Khalilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Purpose. This study aims to develop a conceptual framework for Islamic Circular Economy (ICE) that integrates Sharia principles with circular economy business models in the context of waste management and recycling in Indonesia. The global environmental crisis and waste management challenges demand innovative approaches that are not only economically efficient but also rooted in ethical and spiritual values. This study identifies fundamental convergences between maqasid al-shariah and circular economy principles to establish a theoretical foundation for developing Sharia-based sustainable business models. Materials and methods. The research employs a qualitative-conceptual approach through a systematic literature review of 68 peer-reviewed publications from 2015-2025, covering three domains: circular economy, Islamic economics, and sustainable waste management. Analysis was conducted through conceptual synthesis and comparative analysis to identify principle alignments, research gaps, and integration opportunities between the two paradigms. Results. The study produces an Islamic Circular Economy framework that synergizes five maqasid al-shariah principles (hifz al-din, hifz al-nafs, hifz al-aql, hifz al-nasl, hifz al-mal) with four circular economy pillars (reduce, reuse, recycle, recover). This framework yields four creative business models: (1) Halal Waste-to-Resource Enterprises that transform waste into value-added halal products; (2) Zakat-based Recycling Cooperatives that mobilize productive zakat for community recycling infrastructure; (3) Waqf-based Waste Management Infrastructure that leverages productive waqf for sustainable facility development; and (4) Islamic Social Finance for Circular Startups that integrates Islamic financial instruments for circular economy venture financing. Conclusions. Islamic Circular Economy offers an alternative paradigm bridging economic, ecological, and spiritual dimensions in resource management. The resulting business models contribute theoretically by extending circular economy theory through an Islamic economics perspective, while providing practical implications for policy development and sustainable business practices in Indonesia and other Muslim-majority countries. Further research is needed for empirical validation of the proposed models and comprehensive assessment of their socio-economic-environmental impacts.